A readable TCP in the Prolac protocol language. - Kohler, Eddie (Computer communication review.)
Prolac is a new statically-typed, object-oriented language for network protocol implementation. It is designed for readability, extensibility, and real-world implementation; most previous protocol languages, in contrast, have been based on hard-to-implement theoretical models and have focused on verification. We present a working Prolac TCP implementation directly derived from 4.4BSD. Our implementation is modular---protocol processing is logically divided into minimally-interacting pieces; readable---Prolac encourages top-down structure and naming intermediate computations; and extensible---subclassing cleanly separates protocol extensions like delayed acknowledgements and slow start. The Prolac compiler uses simple global analysis to remove expensive language features like dynamic dispatch, resulting in end-to-end performance comparable to an unmodified Linux 2.0 TCP.